Proficiency in Financial Literacy: study using a scale and a Computerized Adaptive Test based on the Item Response Theory - Capelato, Érika [UNESP]; Cúri, Mariana (FapUNIFESP (SciELO), 2023)
This article presents a study to assess performance in financial literacy in Basic Education. To this end, an instrument was constructed with 27 items published by the Program for International Student Assessment and based on a reference matrix, divided into four themes: money and transactions, financial planning and management, risk and return and financial scenario. These items were organized in test notebooks, with 18 items each, using the Balanced Incomplete Blocks methodology. The notebooks were applied to 316 first-year high school students from public schools of the Education Board of the Araraquara Region - São Paulo. The responses were analyzed from the Item Response Theory, which made it possible to estimate, on the same scale, the skills of the respondents and the parameters of the items. The calibration of the items enabled the construction of a skill scale, which was pedagogically interpreted, and the simulation of a Computerized Adaptive Test (CAT). The simulation result showed that the TAC provides good estimates of the financial literacy skill level with fewer items, which reduces the time and effort normally spent by students in traditional tests.
Proficiência em Letramento Financeiro: estudo a partir de uma escala e de um Teste Adaptativo Computadorizado baseados na Teoria de Resposta ao Item
Keywords: Basic education; Computerized Adaptive Test; Financial literacy; Item Response Theory